Development of juice- based beverage and ripe- fruit powder from banana(musa SPP.) - Evelin A Mary (Department of Processing Technology, College of Horticulture, 2005)
The study on "Development of juice-based beverage and ripe-fruit powder from banana (Musa spp.)" was carried with the objective of developing a drying and packaging regime for ripe banana powder and to develop a beverage based on clarified banana juice. Technology for spray and drum dried banana powder was standardized through drying and packaging experiments. Good quality spray dried banana powder could be obtained with an inlet air temperature of 150°C, keeping the outlet temperature at 100°C with two per cent maltodextrin and three per cent soluble starch on wet basis as additive. Successful drum drying could be achieved with drum temperature of 152°C with drum speed of three rpm and soluble starch 2.5 per cent on wet basis as additive. Drum drying was found better in terms of higher recovery, lesser additive, better quality and lesser cost of production. Moisture sorption studies revealed that banana powder was highly hygroscopic requiring special packaging, techniques. Gas Chromatography-Mass Spectrometry analysis revealed that the caramelized fruity fig like aroma of banana powder was due to Furaneol and Ethyl einnamate. Banana powder could be stored for one year under ambient conditions without deterioration when packed in aluminium foil laminated pouches with nitrogen. Banana powder can be used as an ingredient in baby food, health food, instant beverage mix, breakfast cereals, flavourings, bakery and dairy products. The cost of production of 100 grams of spray and drum dried banana powder worked out to be Rs.26.61 and Rs.18.66 respectively.